Zanubrutinib for the treatment of lymphoid malignancies: Current status and future directions - Wolska-Washer, Anna; Robak, Tadeusz (Frontiers in Oncology, 2023)
Zanubrutinib (BGB-3111, Brukinsa®, BeiGene) is a next-generation irreversible inhibitor of Bruton’s tyrosine kinase (BTK), developed by BeiGene in 2012 for the treatment of B-cell malignancies. It was designed to minimize off-target inhibition of TEC- and EGFR-family kinases. Zanubrutinib is more selective than ibrutinib for BTK vs. EGFR, FGR, FRK, HER2, HER4, ITK, JAK3, LCK, BLK and TEC. In addition, compared to ibrutinib, zanubrutinib has improved oral absorption and better target occupancy. Zanubrutinib demonstrated a lower incidence of off-target toxicities and reduced severity than ibrutinib. Moreover, zanubrutinib is similar to acalabrutinib, with less activity against TEC and ITK. The preliminary phase 1 results suggest that zanubrutinib has clinical activity and the drug is well tolerated in patients with B-cell lymphoid malignancies. Recent clinical trials have found it to demonstrate excellent efficacy and good tolerability in patients with chronic lymphocytic leukemia (CLL), Waldenstrom macroglobulinemia (WM) and mantle cell lymphoma (MCL). In recent phase 3 studies , zanubrutinib was compared with ibrutinib in patients with relapsed/refractory (R/R) MW and RR CLL (Table 1). In both trials, zanubrutinib was found to demonstrate clinically meaningful advantages in safety and tolerability over ibrutinib; in particular, it was associated with a lower risk of atrial fibrillation/flutter and major bleeding events. In the recent SEQUOIA study, comparing zanubrutinib with bendamustin and rituximab (BR) in patients with previously untreated CLL, zanubrutinib significantly improved progression-free survival versus BR, with an acceptable safety profile consistent with previous studies. Zanubrutinib also demonstrated good activity and tolerability in patients with R/R MCL, marginal zone lymphoma and follicular lymphoma. Trials examining the efficacy and safety of the combination of zanubrutinib with obinutuzumab venetoclax and other drugs are ongoing. This review summarizes the clinical efficacy and safety of zanubrutinib in lymphoid malignancies.